Enhancing Students Speaking Skills by Making Video Youtube TUTORIAL AS PROJECT BASED LEARNING - Novita Kusumaning Tyas; Nining Fitriani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The aims of this study were to know how effective of making video tutorial as project-based learning to improve students speaking skills and to know the student’s attitude toward project-based learning. This study employed mix method design, both qualitative and quantitative research design. The researcher used purposive sampling. The selection was based on the characteristics of the population and the purpose of the study. The subjects were 30 students of informatics management program. The result of this study showed that the mean score of experimental group was higher than control group. The pronunciation aspect, the mean of experimental group got score 81.3 and in control group got score 75.07. In grammar aspect the mean score of experimental group was 80.9 and in control group was 73.63.  The mean score of experimental group in vocabulary aspect was 81.4 and the control group was 74.5. The last aspect was fluency, the mean score in experimental group was 80.9 and in control group was 75.03. From the students attitudes also showed good effect toward implementation of project-based learning in improving students’ speaking skill.